DOES AUTHORITATIVE PARENTING STIMULATE CAREER DECISION SELF-EFFICACY IN ADOLESCENT? - Kumala, Intan Dewi; Afriani, Afriani (Psikoislamedia: Jurnal Psikologi, 2023)
Abstract: Career decision making is one of the developmental tasks in adolescence, especially late adolescence (18-21 years), namely determining the specifications of the career that will be undertaken. In this process, the level of efficacy in adolescents are formed through the authoritative type of parental authority is taken into consideration. Parental authority has contributed to the level of adolescent efficacy in making career decisions appropriate. This study aims to determine the relationship between parental authority (authoritative parenting style) and career decision self-efficacy among adolescents in Aceh. The method used was multistage cluster and disproportionate stratified random sampling and data collection was carried out in nine selected areas in Aceh province with a total sample of 347 adolescents aged 18-21 years. The instrument used is the Parental Authority Questionnaire (PAQ) and the Career Decision Self-Efficacy Short Form (CDSE-SF). The results showed that there was a relationship between the two variables, namely a positive relationship between the authoritative father r= 0,797 (p<0,05) and the authoritative mother r= 0,804 (p<0,05) with the CDSE variable. This means that the better type of parental authority according to the adolescent's assessment, the higher efficacy adolescents have in making career decisions (career decision self-efficacy).  Key words: Adolescents;  Parental Authority : Authoritative;  Career Decision Self-Efficacy.